Implementasi Media Literasi Digital Dalam Memotivasi Kebiasaan Kebiasaan Membaca Bagi Peserta Didik Pada Pembelajaran Bahasa Indonesia di SD Negeri 5 Sumerta Denpasar - Sukmadewi, Ni Kadek Diah; Meli, Meli (Jayapangus Press, 2023)
Digital literacy includes individual skills in accessing, processing, learning and conveying information through digital media in line with advances in information and communication technology. This research focuses on the use of digital literacy media in increasing students' reading interest in learning Indonesian at SD Negeri 5 Sumerta Denpasar. This research aims to explore how digital literacy media is applied to increase students' reading interest; identify obstacles and strategies used in implementing digital literacy media to increase students' reading interest; evaluate the impact of using digital literacy media on students' reading interest. The theories used include functionalism, motivation, and constructivism. The research method used is qualitative with a descriptive approach. Data was analyzed through the stages of data collection, data reduction, data display, verification and drawing conclusions. Data validity was confirmed through triangulation of information sources and research instruments. The research results show that the implementation of digital literacy media in Indonesian language learning includes the use of devices such as laptops, LCD screens and cellphones, with stages of development, implementation and evaluation. Obstacles and strategies in using digital literacy media include student, teacher and school environment factors. The implications of using digital literacy media include increasing student creativity, interest in reading, and student curiosity.